Meningkatkan Kemampuan Membaca Al-Qur’an Terhadap Anak SD di Kelurahan Brandan Barat (Dari Desa Kita Bangun Negeri Lewat Pendidikan Kita Bersinergi) - Hasibuan, Ali Daud; Thasfa, Saida Amini; Harahap, Khairunnisa; Sukma, Dasmara; Anggina, Asih; Mariana, Wina (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Mong elementary school children, so this problem should be resolved by providing training in reading the Al-Qur’an properly and correctly to improve their ability. Reciting Al-Qur’an. Based on these problems, community service students majoring in Islamic education counseling 3 UINSU will provide training in learning to read the Al-Qur’an to elementary school children in Brandan Barat Subdistrict with the hope of helping and improving the reading of the Al-Qur’an to elementary school children in the Subdistrict. The. The method used in this activity uses Using qualitative research methods, because the approach taken is through a descriptive qualitative approach, in qualitative research using the results of interviews and observations and training methods for elementary school children in Brandan Barat Subdistrict by conducting training in reading the Al-Qur’an at the homes of residents who are Koran teachers in the new village of Brandan Barat subdistrict. This Al-Qur’an reading training is carried out every evening at the Koran teacher’s house and is assisted by community service students from UINSU. Based on the results of the implementation of the program carried out by UINSU community service students, they will be able to improve the abilities of elementary school children in Brandan Barat Subdistrict both in reading the Al- Qur’an, training in the tone of reading the Al-Qur’an and reading tajwid verses of the Al-Qur’an.